Presence of relaxin-2, oxytocin and their receptors in uterosacral ligaments of pre-menopausal patients with and without pelvic organ prolapse - Schott, Sarah; Reisenauer, Christl; Busch, Christian (Acta obstetricia et gynecologica Scandinavica, 2014)
Objective Pelvic organ prolapse (POP) is a major health concern for women. Its pathophysiology is yet not fully understood. We reported an impaired functional state of the smooth muscle compartment in uterosacral ligaments from patients with POP, which was cholinergic, stimulated by oxytocin and modulated by relaxin-2. The current study investigated the presence of oxytocin and relaxin-2 and their receptors in the uterosacral ligament from POP/non-POP patients. Design Translational investigation on clinical samples. Setting University hospital departments. Population and samples Fourty-three samples of uterosacral ligament from pre-menopausal patients with (n = 20) and without POP (n = 23). Methods Presence of relaxin-2, its receptors RXFP1 and RXFP2, and of oxytocin and its receptor were analysed by immunohistochemistry and classified using a staining score. Additionally, Western blot analysis was performed. Main outcome measures Presence patterns with respect to POP and non-POP uterosacral ligament samples for pathophysiological understanding of POP. Results Relaxin-2, oxytocin and their receptors were expressed in endothelial cells, the smooth muscle compartment and vasa vasorum in the arteries and veins of the uterosacral ligament, in the smooth muscle compartment present in the ground reticulum and in nerves running through the uterosacral ligament. The presence level of relaxin-2 was higher in the uterosacral ligament of the POP cohort (p < 0.001). Conclusions We demonstrated that relaxin-2 had an increased presence in uterosacral ligaments from patients with POP, suggesting a role of the relaxin system in the pathogenesis of POP and identifying the relaxin system as a potential therapeutic target for the pharmacological treatment of POP.